Costa Rica : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in Costa Rica during 1995-97. Costa Rica faced a slump in economic activity in 1995-96 following a sharp deterioration in the public finances and higher inflation associated with the 1993-94 political-economic cycle. To avert a balance-of-payments crisis in early 1995, the authorities increased interest rates, imposed temporary import surcharges, and raised excise taxes, while tightening expenditure and shifting some outlays to 1996. The economy went into a recession in 1996, with private investment declining for a third consecutive year.